1991
DOI: 10.1111/j.1432-1033.1991.tb15895.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of α‐ and βγ‐subunits of G0 to β1‐adrenoceptor in sealed unilamellar lipid vesicles

Abstract: First, we describe a preparation of sealed unilamellar lipid vesicles. When this preparation was subjected to sucrose density gradient centrifugation, two rather uniform fractions emerged, one consisting of lighter lipid-rich vesicles with average diameters ranging over 150 -200 nm (fraction I), the other consisting of heavier vesicles with average diameters ranging over 30 -70 nm (fraction 11). When the lipid mixture containing dimyristoylglycerophosphocholine, cholesterol, dipalmitoylglycerophosphoserine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Additional data indicate that even within the context of G-protein heterotrimers, a receptor may make contact with all three G-protein subunits (45)(46)(47)(48)(49). If so, then it is unclear whether the G␤␥ binding site identified in the i3 loop of the M 3 -MR in the present study is also involved in the interaction between receptor and G␤␥ in G-protein heterotrimers.…”
Section: Dqdmentioning
confidence: 67%
“…Additional data indicate that even within the context of G-protein heterotrimers, a receptor may make contact with all three G-protein subunits (45)(46)(47)(48)(49). If so, then it is unclear whether the G␤␥ binding site identified in the i3 loop of the M 3 -MR in the present study is also involved in the interaction between receptor and G␤␥ in G-protein heterotrimers.…”
Section: Dqdmentioning
confidence: 67%
“…These findings suggest that suramin may function in the same manner as GTP␥S, which promotes the dissociation of G␣ from G␤␥. Suramin has been shown to reduce the affinity of the transducin ␣ subunit for the plasma membrane (Lehmann et al, 2002); this effect can be attributed to disruption of G␣-G␤␥ association because G␤␥ plays a major role in anchoring G␣ to the membrane (Sternweis, 1986;Kurstjens et al, 1991). Moreover, a docking simulation has suggested that the binding site for suramin is in the vicinity of a conserved arginine residue (Arg 201 ) in the switch II region of G␣ (Lehmann et al, 2002); this binding site may extend toward the N terminus in the three-dimensional structure.…”
Section: Discussionmentioning
confidence: 99%
“…Such experiments are essential for future functional studies, since seven-transmembrane-domain receptors are known to activate G-protein only when incorporated in a lipid bilayer [20,311. The availability of large amounts of purified, lipid-reconstituted olfactory receptors will greatly facilitate future research into the area of receptor/ligand recognition and transduction mechanisms in the superfamily of olfactory receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid vesicles were prepared a5 described [20]. A mixture (total 200 mg) of dimyristoylglycerophosphocholine, cholesterol, dipalmitoylglycerophosphoserine and dipalmitoylglycerophosphoethanolamine (Sigma) in a molar ra-…”
Section: Receptor Peptidementioning
confidence: 99%